2016
DOI: 10.1002/jnr.23958
|View full text |Cite
|
Sign up to set email alerts
|

Simulated microgravity enhances oligodendrocyte mitochondrial function and lipid metabolism

Abstract: The primary energy sources of mammalian cells are proteins, fats, and sugars that are processed by well-known biochemical mechanisms that have been discovered and studied in 1G (terrestrial gravity). Here we sought to determine how simulated microgravity (sim-µG) impacts both energy and lipid metabolism in oligodendrocytes (OLs), the myelin-forming cells in the central nervous system. We report increased mitochondrial respiration and increased glycolysis 24 hr after exposure to sim-µG. Moreover, examination of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 29 publications
(34 reference statements)
3
19
0
Order By: Relevance
“…These intermediates can act as signaling molecules and control immune responses through regulating cytokine production from immune cells [ 54 ]. Changes in fatty acids following exposure to space radiation have been reported previously, not only in astronauts [ 15 ], but also in tissues from HZE exposed animals and spaceflight animals [ 56 , 57 ] and microgravity stimulated studies [ 58 ], including increased expression of enzymes such as COX2 [ 59 ]. Given also that common themes emerge for responses such as radiation or microgravity, it is imperative to investigate in future studies whether combined stressors (including CO2 and sleep deprivation among others) can lead to heightened responses and whether effective countermeasures can be designed to address some of the underlying metabolic changes.…”
Section: Discussionmentioning
confidence: 91%
“…These intermediates can act as signaling molecules and control immune responses through regulating cytokine production from immune cells [ 54 ]. Changes in fatty acids following exposure to space radiation have been reported previously, not only in astronauts [ 15 ], but also in tissues from HZE exposed animals and spaceflight animals [ 56 , 57 ] and microgravity stimulated studies [ 58 ], including increased expression of enzymes such as COX2 [ 59 ]. Given also that common themes emerge for responses such as radiation or microgravity, it is imperative to investigate in future studies whether combined stressors (including CO2 and sleep deprivation among others) can lead to heightened responses and whether effective countermeasures can be designed to address some of the underlying metabolic changes.…”
Section: Discussionmentioning
confidence: 91%
“…With respect to lipid metabolism, microgravity exposure also increased lipid synthesis in the skeletal system, as observed in the fatigued muscle cells 34 , which shifts from lipid toward glucose metabolism. The reduced glycerol shuttle, increased triglycerides production, shifting metabolism toward a higher reliance on lipids 47 . The increased lipid production was also paralleled by a reduction in beta oxidation of fatty acids inside the mitochondria, as indicated by a significant increase in acyl-CoA concentration and the concomitant decrease of acyl-carnitine (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the present study investigated whether 1 and 3 days exposure to SMG could influence the metabolites of human HGC-27 gastric cancer cells. Previous studies have demonstrated that SMG influences several metabolic pathways, stimulates lipid metabolism and interrupting the Krebs cycle in human breast cancer cells, osteoblast and oligodendrocyte after 5 d, 110 h and 3 d of SMG, respectively (26,27,37).…”
Section: Discussionmentioning
confidence: 99%